PELAKSANAAN PEMILU 2019 DI KABUPATEN MESUJI: KUALITAS KERJA KPPS - Melinasari, Runi; Hertanto, Hertanto; Warganegara, Arizka; Maryanah, Tabah (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
The 2019 general election was the first simultaneous election with 5 ballot boxes. With such conditions, election organizers are required to be able to work in accordance with changes in applicable rules. The Voting Organizing Group (KPPS) as the organizer of elections at polling stations (TPS) is the spearhead of the implementation of voting and counting of votes, but various problems occur in the implementation of voting and counting of votes carried out by KPPS in the 2019 elections in Mesuji Regency. The research was carried out through a literature study using secondary data types and limited the focus on the problem of KPPS work quality in writing and copying C1 forms in the 2019 elections in Mesuji Regency. The KPU is committed to conducting elections transparently through the publication of election results. KPU Regency/City as the executor of the scan and entry of Form C1 into Situng is not allowed to make improvements to form C1 which has a writing error by KPPS. Errors in the writing of form C1 were corrected in the recapitulation of the results of the counting of votes at the district level. Likewise, improvements are carried out in stages up to the national level. With such a procedure, when the public and stakeholders access preliminary information about the results of the votes from the C1 form that has been scanned and entered it turns out that there is an error, it will cause public distrust of the election results. This kind of phenomenon occurs in the KPU of Mesuji Regency. In the 2019 elections in.